Прецизионное точение алюминиевого сплава АМГ-6 алмазным наноструктурным инструментом - Розенберг, О.А.; Шульженко, А.А.; Сохань, С.В.; Соколов, А.Н.; Боженок, В.Н.; Шуляковский, Н.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Changing roughness character of surface of alumina alloy AMG-6 is investigated at a precision turning by diamond nanostructural tool based on diamond powder with initial graininess of
ACM5 0,1/0 and ACM5 0,5/0,1. Moreover, effect is investigated of sharpening cutting edge on
roughness.